Age-related penetrance of the C9orf72 repeat expansion - Natalie A. Murphy (Nature Portfolio, 2017)
Abstract A pathogenic hexanucleotide repeat expansion within the C9orf72 gene has been identified as the major cause of two neurodegenerative syndromes, amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). This mutation is known to have incomplete penetrance, with some patients developing disease in their twenties and a small portion of carriers surviving to their ninth decade without developing symptoms. Describing penetrance by age among C9orf72 carriers and identifying parameters that alter onset age are essential to better understanding this locus and to enhance predictive counseling. To do so, data from 1,170 individuals were used to model penetrance. Our analysis showed that the penetrance was incomplete and age-dependent. Additionally, familial and sporadic penetrance did not significantly differ from one another; ALS cases exhibited earlier age of onset than FTD cases; and individuals with spinal-onset exhibited earlier age of onset than those with bulbar-onset. The older age of onset among female cases in general, and among female bulbar-onset cases in particular, was the most striking finding, and there may be an environmental, lifestyle, or hormonal factor that is influencing these penetrance patterns. These results will have important applications for future clinical research, the identification of disease modifiers, and genetic counseling.